Coastal SAR and PLRM altimetry in German Bight and West Baltic Sea. Issue 6 (15th September 2018) - Dinardo, Salvatore; Fenoglio-Marc, Luciana; Buchhaupt, Christopher; Becker, Matthias; Scharroo, Remko; Joana Fernandes, M.; Benveniste, Jérôme
Abstract: Unlike previous altimetric missions, the CryoSat-2 altimeter features a novel Synthetic Aperture Radar (SAR) mode that allows higher resolution and more accurate altimeter-derived parameters in the coastal zone, thanks to the reduced along-track footprint. The scope of this study is to quantify regionally the skills of CryoSat-2 SAR altimetry for distances to coast smaller than 10 km, during the mission lifetime and at different time scales. The validated geophysical altimeter parameters are the sea surface height above the ellipsoid, the significant sea wave height and wind speed, all computed at 20 Hz. These have been compared to in situ and regional model data along the coasts of German Bight and West Baltic Sea during a time interval of almost six years, from July 2010 to March 2016, to investigate both instantaneous and seasonal behaviour. From CryoSat-2 FBR (Full Bit Rate) data, a Delay-Doppler processing and waveform retracking tailored specifically to the coastal zone has been carried out, by applying a Hamming window and zero-padding, using an extended vertical swath window in order to mitigate tracker errors. Moreover, a dedicated SAMOSA-based coastal retracker (here referred to as SAMOSA+) has also been implemented. Since one of the highest remaining uncertainties in the altimeter parameters estimated in coastal shallow waters arises from residual errors in the applied range and geophysical corrections, innovative and high resolution solutions for ocean tide model, geoid, mean sea surface and wet tropospheric correction have been selected. As CryoSat-2 SAR and LRM (Low Rate Mode) modes are not collocated in time, in order to quantify the improvement in the coastal zone with respect to pulse-limited altimetry, 20 Hz PLRM (pseudo-LRM) data from CryoSat-2 FBR were built and retracked, adopting the ALES adaptive sub-waveform approach, with a numerical Brown-based retracker, here referred to as TALES. The cross-validation proves the good consistency between PLRM and SAR sea level anomaly in the coastal zone. The regional ocean model (BSH) shows the highest agreement with the SAR sea level anomaly, with a standard deviation of the differences (stdd) of 24 cm, whereas the corresponding value with respect to PLRM is 55 cm. Distance to coast plots show that land contamination begins to affect sea level and wave measurements at 2 km from the coast in SAR and at 3.5 km in PLRM TALES. The analysis of monthly mean time-series shows that SAR Altimetry is able to measure the sea level monthly mean in the coastal zone of the region of interest, during the entire mission, more precisely than PLRM. The cross-validation against in situ data also proves the higher accuracy of SAR SAMOSA+ compared to PLRM TALES in the coastal zone, with average SLA stdd of 4.4 cm and 8.4 cm respectively.